Love's Beauty At the Heart of the Christian Moral Life The Ethics of Catholic Theologian Hans Urs von Balthasar. - Barrett, Melanie Susan (Lewiston : Edwin Mellen Press, 2009)
This study develops the ethical theory implicit in the writings of Hans Urs von Balthasar, a prominent twentieth-century Swiss Catholic theologian. Balthasar's attempt to critically retrieve the concept of beauty for Christian theology yields important ethical insights, culminating in an aesthetic and dramatic theory of ethics: one in which the perception of the beauty of God's love in Christ becomes a foundational experience for moral formation and ongoing ethical discernment.
Chapter 4: The Christian Moral LifeIV.1. Becoming Virtuous: Christ as Concrete Ethical Norm; IV.2. Love's Perfectionist Orientation: All Are Called to Love Perfectly; IV.3. The Process of Moral Formation; IV.4. Conclusion; Chapter 5: Further Refining Balthasar's Ethics; V.1. Christian Moral Judgment; V.2. Conclusion: Critiquing Balthasar's Ethics; Bibliography; Index
Description based upon print version of record.
Keywords: Aesthetics -- Religious aspects -- Catholic Church; Balthasar, Hans Urs von, 1905-1988.; Christian ethics -- Catholic authors; God (Christianity) -- Beauty; God (Christianity) -- Love; Love -- Religious aspects -- Catholic Church; Philosophy; Religion; Balthasar, Hans Urs von, -- 1905-1988.; Christian ethics -- Catholic authors; God (Christianity) -- Love; God (Christianity) -- Beauty; Love -- Religious aspects -- Catholic Church; Aesthetics -- Religious aspects -- Catholic Church; RELIGION / Christian Theology / Ethics; Electronic books